2021
DOI: 10.1109/tcyb.2020.3009128
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Output-Feedback Control for Discrete-Time Fuzzy Systems With Local Nonlinear Models Subject to State and Input Constraints

Abstract: This paper presents a new approach to design static output feedback (SOF) controllers for constrained Takagi-Sugeno fuzzy systems with nonlinear consequents. The proposed SOF fuzzy control framework is established via the absolute stability theory with appropriate sector-bounded properties of the local state and input nonlinearities. Moreover, both state and input constraints are explicitly taken into account in the control design using set-invariance arguments. Especially, we include the local sector-bounded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…in the consequents of the N-TS fuzzy system (6), N-TS fuzzy modeling allows reducing significantly the number of fuzzy rules compared with the classical TS fuzzy modeling, especially for complex nonlinear systems. 46,53 Hence, N-TS fuzzy-model-based approaches can lead to less conservative results and less computational burden compared with those based on the classical TS fuzzy modeling. 26,51 For descriptor observer design, we rewrite system (6) in the following equivalent singular form:…”
Section: Description Of N-ts Fuzzy Descriptor Systemsmentioning
confidence: 99%
“…in the consequents of the N-TS fuzzy system (6), N-TS fuzzy modeling allows reducing significantly the number of fuzzy rules compared with the classical TS fuzzy modeling, especially for complex nonlinear systems. 46,53 Hence, N-TS fuzzy-model-based approaches can lead to less conservative results and less computational burden compared with those based on the classical TS fuzzy modeling. 26,51 For descriptor observer design, we rewrite system (6) in the following equivalent singular form:…”
Section: Description Of N-ts Fuzzy Descriptor Systemsmentioning
confidence: 99%
“…In particular, reduced-complexity feedback controller is still able to guarantee the closed-loop properties defined in Problem 1. For this purpose, we rewrite some premise variables as follows (Nguyen et al, 2020a)…”
Section: Reduced-complexity Fuzzy Tracking Controlmentioning
confidence: 99%
“…In recent years, lateral control of autonomous vehicles has attracted great attention from academic [2] and industrial communities [3,4] and many results have been reported [5][6][7]. Some authors suggest new lateral control system architecture by combining the fuzzy logic and PID control [8].…”
Section: Introductionmentioning
confidence: 99%